Analysis EDFA Gain in OCDMA System for Fiber-to-the-Home Network - Ahamed, Nizam Uddin; Ahmed, Nasim; Ali, Md. Sharafat; Ahmad, Badlishah; Rahman, S. A. M. Matiur (IAMOT, 2014)
In this paper, the optimum EDFA gain is analyzed for an optical code division multiple access (OCDMA) at different bit rates for 30 km transmission distance. The Enhance Double Weight (EDW) code is used as a signature address of the system because this code can accommodate more number of simultaneous users under considerable standard Bit-Error-Rate (e.g. â‰¤ 10E-9). In addition, this system receiver is designed using NAND subtraction technique to produce better signal and increase the bit-error-rate (BER) performance and maintain error floor transmission rate (10E-9). The extensive theoretical and simulation has been taken into the account to carry out analysis. We ascertained from our analysis results that the proposed detention technique significantly improves the signal quality and require low optimum gain of the system. Therefore, this system is considered as a promising solution for Fiber-to-the-Home access network.